Intrapartum transperineal ultrasound assessment of fetal head progression in active second stage of labor and mode of delivery. (25th March 2013) - Ghi, T.; Youssef, A.; Maroni, E.; Arcangeli, T.; De Musso, F.; Bellussi, F.; Nanni, M.; Giorgetta, F.; Morselli‐Labate, A. M.; Iammarino, M. T.; Paccapelo, A.; Cariello, L.; et al.
ABSTRACT Objective To compare longitudinal changes in angle of progression (AoP) and midline angle (MLA) during the active second stage of labor according to the mode of delivery. Methods A three‐dimensional transperineal ultrasound volume was acquired in a series of nulliparous women at the beginning of the active second stage (T1) and every 20 min thereafter (T2, T3, T4, T5 and T6). Following delivery, all ultrasound volumes were analyzed and AoP and MLA were measured. Results Among 71 women included in the study, 58 underwent spontaneous vaginal delivery (Group A) and 13 underwent operative delivery (Group B) (eight by vacuum extraction and five by Cesarean section). When compared with Group B, Group A had a wider AoP only at T1 (140.0 ± 20.2° vs 122.9 ± 16.7°; P = 0.010) and T2 (149.7 ± 20.7° vs 126.9 ± 17.5°; P = 0.006). MLA was narrower in Group A only at T3 (21.2 ± 11.7° vs 40.8 ± 27.9°; P = 0.043), T4 (18.2 ± 15.0° vs 47.4 ± 29.6°; P = 0.020) and T5 (18.3 ± 6.0° vs 34.7 ± 4.2°; P = 0.034). On stepwise forward multiple logistic regression analysis, both AoP and MLA were independently associated with operative delivery (OR = 0.955 and OR = 1.018, respectively). Conclusion Ultrasonographic assessment of fetal head descent in the second stage of labor may play a role in the prediction of the mode of delivery. Copyright © 2013 ISUOG. Published by John Wiley & Sons, Ltd.